Pembelajaran Dengan Model Kooperatif Tipe Jigsaw Dan Pendekatan Ilmiah Terhadap Kemampuan Siswa Dalam Pemahaman Konsep Dan Pemecahan Masalah Pada Sistem Persamaan Linear Tiga Variabel di kelas X SMA Swasta Raksana Medan T.P 2019/2020 - Rizki Agnes Simanjuntak (LPPM Universitas HKBP Nommensen, 2024)
In this study, the test instruments used were mathematical concept understanding and mathematical problem solving test instruments. The population in this study were students of class X SMA Sawasta Raksana Medan odd semester 2019/2020 academic year consisting of 3 classes, namely X IPA 1, X IPA 2, and X IPA 3. This study aims to improve students' ability to solve problems and understand concepts in learning the system of linear equations of three variables. Based on Table 4.15, the results obtained tcount = 1.733 and ttable = 1.671 (tcount> ttable) which means Ha2 is accepted. Thus it can be concluded that learning with the Jigsaw II type cooperative model is better than the scientific approach to problem solving on the system of linear equations of three variables in class X SMA Swasta Raksana Medan TP 2019/2020. Keywords: Jigsaw Type Cooperative, Concept Understanding and SMA Swasta Raksana Medan